2014
DOI: 10.1038/ncomms5820
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of NF-κB activity by brain-specific TRIpartite Motif protein 9

Abstract: The TRIpartite Motif (TRIM) family of RING-domain-containing proteins participate in a variety of cellular functions. The β-transducin repeat-containing protein (β-TrCP), a component of the Skp-Cullin-F-box-containing (SCF) E3 ubiquitin ligase complex, recognizes the NF-κB inhibitor IκBα and precursor p100 for proteasomal degradation and processing respectively. β-TrCP thus plays a critical role in both canonical and non-canonical NF-κB activation. Here, we report TRIM9 is a negative regulator of NF-κBactivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 57 publications
1
60
0
Order By: Relevance
“…Extending these studies, a recent report identified TRIM5 as a regulator of autophagy that acts as a restriction factor against HIV-1 (Mandell et al, 2014). TRIM family members largely function in negative regulatory circuits, as was recently demonstrated for TRIM9, a negative regulator of NF-κB pro-inflammatory cytokine signaling (Shi et al, 2014). An increasing number of TRIM proteins have also been described as enhancers of innate immune pathways, as in the case of TRIM44 stabilizing MAVS to enhance signaling (Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…Extending these studies, a recent report identified TRIM5 as a regulator of autophagy that acts as a restriction factor against HIV-1 (Mandell et al, 2014). TRIM family members largely function in negative regulatory circuits, as was recently demonstrated for TRIM9, a negative regulator of NF-κB pro-inflammatory cytokine signaling (Shi et al, 2014). An increasing number of TRIM proteins have also been described as enhancers of innate immune pathways, as in the case of TRIM44 stabilizing MAVS to enhance signaling (Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…The purification of mouse cGAS protein including the unnatural amino acid was described previously (Shi et al, 2014). Briefly, the Ser291 (AGC) codon was replaced by the pSer291 (UAG) amber codon by site-directed mutagenesis (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…TRIM9 is highly expressed in the central nervous system [26,27]. Recently, TRIM9l was reported to negatively regulate NF-κB signaling by preventing β-TrCP binding to its substrate IκB [28]. However, the role of TRIM9 in virus-induced type I IFN signaling and inflammation is still not clear.…”
Section: Introductionmentioning
confidence: 94%
“…It has been reported that the phosphorylation of TRIM9 at its RING domain (Ser76 and Ser80) is critical for its inhibitory effect on NF-κB signaling [28]. We examined whether TRIM9s-mediated type I IFN activation is also dependent on TRIM9s phosphorylation.…”
Section: Trim9 Promotes Tbk1-mediated Signaling Through Its E3 Ligasementioning
confidence: 99%
See 1 more Smart Citation